Pengaruh Variasi Diameter Injektor Konvergen Udara Terhadap Fenomena Flooding Dalam Aliran Dua Fase Gas-Cair Berlawanan Arah Pada Pipa Vertikal - Wahyudi, Noorsakti; Soenoko, Rudy; Wahyudi, Slamet (Jurnal Rekayasa Mesin, 2013)
One type of multi-phase flow is the flow of gas-liquid two-phase. Two-phase flow is widely used in daily life and industry. One type of two-phase flow is air-liquid two-phase flow in opposite directions vertically. In the two phase flow of air-liquid in the pipe flooding, phenomenon in the opposite direction is a loss, so it should be avoided or restricted. To overcome this problem then we make the air injector to get the air superficial velocity corresponding. The design of injector that with shaped nozzle has varies diameter out. They are 4 mm, 6 mm and 8 mm. These varies diameter out of nozzle will be examined to find which one of the diameter out nozzle that can slow the flooding that can be seen in the most of the parameters such as superficial velocity, air flow and flow patterns. The results of these research showed that the varies d-out that has the ability to handle debit and best superficial velocity in a row is shaped air injector nozzle with diameter out of 8 mm, 6 mm, 4 mm. The greater the air flow and air superficial velocity the faster flooding occurs. Flow pattern before the onset of flooding is annular flow pattern. Flow pattern at the beginning of the flooding was wispy annular. And flow pattern at the time of the total flooding is churn flow pattern.Keywords : two phase, counter current flow, flooding, air injector, flow regime.